The status of virgins according to the works of St. Ambrose of Milan - Andrey Posternak (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви, 2024)
The article examines the position and ministry of virgins at the end of the 4th century in the Early Church in the West as a new Church institution based on the works of St. Ambrose. In modern historiography, this issue is usually considered in the specifi c historical conditions of the ministry of the bishop of Milan, without analysis of the order of virgins as an ecclesiastical institution. Various aspects of the status of virgins as members of the Church order are considered according to the works of St. Ambrose: age, consecration, requirements for chastity and general lifestyle. By the end of the 4th century, the institutionalisation of female asceticism was gradually taking place in the West, and St. Ambrose actively participated in the formation of the tradition of the religious status of virgins, according to which joining their community took place through the consecration of a bishop by a special order, and violation of chastity was a canonical crime. The material and spiritual life of virgins was strictly regulated by mandatory, though not formally prescribed norms, e.g. wearing special vestment, prayer and fasting. Virgins could stay in their homes or live in communities, but asceticism in the home would not be an alternative to “protomonastic” communities appeared also in the time of the bishop of Milan. St. Ambrose is reasonably considered the founder of the proto-monastic female tradition in the Early Church in the West.